GWAS of 89,283 individuals identifies genetic variants associated with self-reporting of being a morning person - Youna Hu (Nature Portfolio, 2016)
Circadian rhythms and related behaviours vary across individuals. Here, a large genome-wide association study reveals common single nucleotide variants influencing whether an individual reports as being a ‘morning person’ by identifying 15 significant loci, including 7 near known circadian genes.